أثر التدريب الذهني لبعض المهارات النفسية في التقليل من مستوى قلق المنافسة الرياضية - بزيو, الدكتور سليم; بزيو،, الأستاذ عادل (Sciences de l'Homme et de la Société, 2015)
إن التدريب الذهني يعتبر أحد الأساليب الحديثة المستخدمة في اكتساب المهارات الحركية وتطويرها، إلى جانب الإعداد للمنافسات والإنجازات الرياضية العالية التي تتطلب قدرًا كبيرًا من استخدام المهارات النفسية العقلية وإصدار القرارات، لذا يجب التركيز عليها خلال التدريب قبل الوصول إلى المنافسات. Abstract : Mental training is one of the followed modern methods in acquiring and developing motor skills, in addition to the preparation of athletes to different competitions and performances of high level, which require an intense and regular use of mental and psychological skills. Consequently, it is notable to advise coaches to integrate them in training before any competition.